[squatters]. - Museu Serralves - Museu de Arte Contemporânea Porto; Fernandes, Joao; von Hafe Perez, Miguel; Marí, Bartomeu; Todoli, Vicente (Porto : Fundação de Serralves, 2001)
Alves da Silva, Augusto ; Alÿs, Francis ; Atelier van Lieshout ; Bartolini, Massimo ; Cruz, Juan ; Damasceno, José ; Estrela, Alexandre ; Ferreira, Angela ; Fischer, Urs ; Flores, Livia ; Floyer, Ceal ; Framis, Alicia ; Gabellone, Giuseppe ; Garrido, Patricia ; Hernández-Diez, José Antonio ; Hoegen, Philippine ; Hugonnier, Marine ; Van Imschoot, Jan ; Islam, Runa ; Kahrs, Johannes ; Koch, Lucia ; Manders, Mark ; Mik, Aernout ; Nicolai, Olaf ; O'Byrne, Lorcan ; Ortega, Damián ; Palma, Miguel ; Pereira, Fernando José ; Queiros, Francisco ; Rauch, Neo ; de Rijke, Jeroen ; Robijns, Gert ; de Rooij, Willem ; Scurti, Franck ; Starling, Simon ; Stratmann, Veit ; Toderi, Grazia ; Tone Scientists ; Tropa, Francisco ; Trouvé, Tatiana ; Vasconcelos, Joana ; Vece, Costa ; Vezzoli, Francesco
[squatters], Museu Serralves - Museu de Arte Contemporânea, Porto, June 23 through September 16, 2001
Portugees & Engels
boek